Structured Plurality Reconsidered. (8th December 2020) - Grimau, Berta
Abstract: In this article, I address the question of the semantic analysis of structured plurals, that is, expressions like these children and those children, which seem to refer to pluralities of individuals divided into groups. In the first half of the article, I describe a variety of structured plural expressions and predicates they can combine with and I point out the difficulties faced by two extant approaches to the semantics of plurals: inflationary and cover-based semantics. In the second half of the article, I propose an alternative account which combines elements from both of them. The main novelty of my proposal is that, by capitalising on the background operation of certain pragmatic principles, it correctly formalises the fact that some interpretations of ambiguous sentences involving structured plurality are more accessible than others.